Hate Speech in the Comment Sections of Social Media Accounts (Tik Tok) “Shafeea Ahmad” - Khotimah, Husnul; Ifan Iskandar; Dewanti, Ratna (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
With the rapid development of social media, the phenomenon of hate speech on digital platforms has increasingly gained global attention, including in Indonesia. TikTok, as a platform with short video formats, has become a busy space for interaction, but also a medium for the emergence of hate speech. This article aims to analyze the phenomenon of hate speech in the comment sections of TikTok account Shafeea Ahmad, focusing on the types of implicatures contained within them. Using a descriptive qualitative approach, this research explores various forms of hate speech, such as implicatures of insult, warnings, anger, annoyance, and provocation found in netizens' comments. The results of the study show that hate speech occurring in TikTok comment sections can damage individual reputations, create social tensions, and worsen the mental health of victims. Therefore, a more considerate approach in commenting on social media is needed to create a safer digital space.